I, too, sing America : the story of Langston Hughes - Rhynes, Martha E., 1929- (Greensboro, N.C. : M. Reynolds, 2002)
A biography of a man who, from the 1920s Harlem Renaissance through the 1960s, wrote poems, stories, and books which celebrated his African American heritage.
Includes bibliographical references (p. 136-138) and index.
Booklist
Bulletin (Center for Children's books)
7.1
5-8
Keywords: Hughes, Langston, -- 1902-1967 -- Juvenile literature; Poets, American -- 20th century -- Biography -- Juvenile literature; African American poets -- Biography -- Juvenile literature; Hughes, Langston, -- 1902-1967.; Poets, American; African Americans -- Biography; Hughes, Langston, -- 1902-1967.; American poets -- Biography; African Americans -- Biography